EFEKTIVITAS PENERAPAN PRINSIP-PRINSIP PEMBIAYAAN PENDIDIKAN DI KABUPATEN REMBANG - Wijayanti, Dwi Rahayu; Lestari, Hendang Zeta; Astuti, Cahyo Puji; Nurkolis, Nurkolis (Dharmas Education Journal (DE_Journal), 2024)
The principles in managing education funds consist of the principles of justice, the principles of efficiency, the principles of transparency and the principles of public accountability. The aim of this research is to determine the effectiveness of implementing the principles of financing junior high school education in Rembang Regency. This research method is quantitative and qualitative descriptive research. The research was conducted at three junior high schools in Rembang Regency using purposive sampling techniques. The subjects of this research were the school principal and school treasurer. The validity of the research uses a dual method, namely interviews and filling out questionnaires. The results of this research are: (1) the application of the principles of justice in education financing in Rembang Regency is in the "good" category; (2) the application of efficiency principles in education financing in Rembang Regency is in the "very good" category; (3) the implementation of the principle of transparency in education financing in Rembang Regency is in the "very good" category; and (4) the implementation of the principle of public accountability in education financing in Rembang Regency is in the "very good" category. Implications of efforts to understand the extent to which the principles of education financing have been implemented effectively in Rembang Regency.